Penafsiran Ayat Al-Quran Tentang Kriteria Pemimpin Ideal - Mhd. Zidan Firmansyah; Miftahul Jannah; Fatma Mulyana Asri; Jendri Jendri (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
Leadership in Islam is based on the principle of monotheism, namely the belief that humans only submit to the leadership of Allah SWT. Leadership characteristics in Islam have their own characteristics because they carry out a big mission in conveying Islamic teachings. The Qur'an comprehensively regulates various aspects of life, including the concept of an ideal leader, which aims to create peace and prosperity in society. Islam sees humans as caliphs on earth, in accordance with the provisions of the Koran. This article aims to explore the verses of the Qur'an that discuss leadership, as well as formulate the goals and characteristics that an ideal leader must have from the perspective of the Qur'an. Some of the characteristics of an ideal leader identified by the author include: First, Al-Ilm (knowledgeable), and second, Mujahid (warrior). who always fights. Third, Mutay (someone who always makes sacrifices). Fourth, a caliph has potential, and is actually able to distance himself from desires in carrying out his leadership. Fifth, Mutajarrid (someone who has full and total commitment).